2004
DOI: 10.1038/sj.npp.1300417
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction Between NMDA and mGlu5 Receptors: Effects on Working Memory, Instrumental Learning, Motor Behaviors, and Dopamine Release

Abstract: Pharmacological manipulation of N-methyl-D-aspartate (NMDA) receptors may be critical for the treatment of many neurological and psychiatric disorders. Metabotropic glutamate (mGlu5) receptors are abundant in corticolimbic circuitry, where they modulate NMDA receptor-mediated signal transduction. Therefore, pharmacological manipulation of mGlu5 receptor may provide a treatment strategy for cognitive disorders that are associated with NMDA receptor dysfunction. We sought to determine whether the recently descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
188
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(201 citation statements)
references
References 59 publications
11
188
1
1
Order By: Relevance
“…A functional interactions between mGluR5 and NMDAR is well supported by the literature (Salter and Kalia, 2004) and our own data (Jia et al, 1998;Huang et al, 2001;Hannan et al, 2001). Indeed, several observations have shown that agonists and antagonists of mGluR5 may, respectively, attenuate and potentiate the effects of NMDAR antagonists in vivo (Kozela et al, 2003;Kinney et al, 2003;Homayoun et al, 2004). As mGluR5 antagonist administered alone could not disrupt PPI, but could enhance the effects of PCP (Kinney et al, 2003), it is possible that the PPI deficit in mGluR5 mutants might result from an interaction between NMDAR hypofunction together with missing mGluR5 complex rather than the alternative of only a parallel pathway downstream of mGluR5.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…A functional interactions between mGluR5 and NMDAR is well supported by the literature (Salter and Kalia, 2004) and our own data (Jia et al, 1998;Huang et al, 2001;Hannan et al, 2001). Indeed, several observations have shown that agonists and antagonists of mGluR5 may, respectively, attenuate and potentiate the effects of NMDAR antagonists in vivo (Kozela et al, 2003;Kinney et al, 2003;Homayoun et al, 2004). As mGluR5 antagonist administered alone could not disrupt PPI, but could enhance the effects of PCP (Kinney et al, 2003), it is possible that the PPI deficit in mGluR5 mutants might result from an interaction between NMDAR hypofunction together with missing mGluR5 complex rather than the alternative of only a parallel pathway downstream of mGluR5.…”
Section: Discussionsupporting
confidence: 55%
“…The mGluR5 binds through G-dependent or independent pathways (Heuss et al, 1999) with predominantly couple via Gq to phospholipase C. This yields diacylglycerol, which activates protein kinase C (PKC), and inositol-1,4,5-triphosphate, which releases intracellular Ca 2 + (Conn and Pin, 1997), and this in turn can increase NMDAR-evoked responses in a variety of neuronal tissues (Doherty et al, 1997;Awad et al, 2000), indicating one potential functional link between mGluR5 and NMDAR. Indeed, administration of mGluR5 antagonist 2-methyl-6-(phenylethynyl)pyradine (MPEP) facilitated in vivo effects of NMDAR antagonists in rodents, producing anxiolytic (Spooren et al, 2000), neuroprotective (Bruno et al, 2000), and anticonvulsant (Chapman et al, 2000) effects, disrupting prepulse inhibition (PPI) (Kinney et al, 2003) and enhancing the detrimental effects of MK-801 on cognition and stereotypy (Homayoun et al, 2004). This demonstrates that mGluR5 play a major role in regulating NMDAR-dependent function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, schizophrenia has been associated with NMDA receptor hypofunction (Javitt and Zukin, 1991;Tamminga, 1998). In rats, PCP and the more potent and selective noncompetitive NMDA antagonist, dizocilpine (MK-801), bring about hyperlocomotion and stereotypies (Hertel et al, 1996;Adams and Moghadam, 2001;Homayoun et al, 2004). These behaviors are thought to result from increased dopaminergic and serotonergic activities (Giros et al, 1996;Jentsch et al, 1998;Lucki, 1998), and have been potentially related to positive symptoms of schizophrenia (Moghaddam and Adams, 1998;Jentsch and Roth, 1999;Mohn et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the mGlu5 receptor antagonist 2-methyl-6-(phenylethynyl)pyridine (MPEP) potentiates the effects of NMDA receptor antagonists on spontaneous burst and spike activity of cortical neurons (Homayoun and Moghaddam 2006). Behavioral studies also show that MPEP enhances the effects of NMDA antagonist blockade on prepulse inhibition, locomotion, working memory, and instrumental learning impairments (Campbell et al 2004;Homayoun et al 2004;Kinney et al 2005a;Spooren et al 2000). The worsening of the detrimental effects of NMDA receptor antagonists by mGlu5 receptor antagonist suggests that activation of mGlu5 receptors may represent a plausible approach for ameliorating symptoms of schizophrenia (Marino and Conn 2002;Moghaddam 2004).…”
mentioning
confidence: 99%